PREDICTION OF TRANSITION OF LATENT TUBERCULOSIS IN CLINICALLY SIGNIFICANT FORM IN CHILDREN WITH TURN OF TUBERCULIN TESTS OR HYPER REACTION TO TUBERCULIN - T.E. Tyul'kova; A.S. Kornachev (Вопросы современной педиатрии, 2011)
Change of tolerance to the tuberculin is the predictor of the infection with Mycobacterium tuberculosis (MBT) and high risk of clinically significant tuberculosis. Besides, phthisiatritians need integral objective criteria for the estimation of anti-infectious immunity. Objective: to evaluate prognostic value of risk factors of clinically significant tuberculosis development in children with changed tolerance to tuberculin. Methods: the study included children with turn of tuberculin test or hyper reaction to the tuberculin (the size of papule must be 17 мм). The risk of tuberculosis development was estimated by multifactorial modeling. All patients from high risk group (n = 29) received preventive chemotherapy (isoniazid or its combination with pyrazinamide), parents of all children with low risk of tuberculosis (n = 20) refused anti-tuberculosis treatment. Results: changes of tolerance to tuberculin and the size of papule were equal in both groups: mean difference for children with high risk is 3.2 mm (95% CI 0.7–5.7), for children with low risk — 2.4 mm (95% CI 0.1–4.7). At the time of first examination, X-ray changes in lungs (intensification of vascular reflection, hypoplasia of pulmonary artery, thickening of pleura, presence of calcified focuses) were detected in 6 (21%) patients from high risk group. Repeated examination was performed in 12 months. Calcified focuses in intrathoracic lymphonodules were revealed in another one child from this group. Conclusion: prognostic criteria of tuberculosis show objective need of preventive treatment. In case of absence of these criteria further observation of children by general practitioners is recommended.Key words: children, tuberculosis, immune system, diagnostics, chemotherapy.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 65–69)